An integrative approach to elucidate and enhance hygienic practices in small-scale poultry slaughterhouses in northern Thailand - Chotinun, S.; Rojanasthien, S.; Unger, Fred; Suwan, M. (Veterinary Public Health Centre for Asia Pacific, 2013)
In Thailand small scale rural poultry production development can be challenged by food safety policies that limit economic development opportunities. This may limit incentives for improving sanitation and disease prevention. Therefore, the project funded by the International Development Research Centre and implemented by International Livestock Research Development was performed. In this study integrative research including a participatory approach was used to elucidate and enhance the hygienic practices in small scale poultry slaughterhouses in rural Northern Thailand. Initial steps included the identification of stakeholders associated with meat production chain, development of a research framework, and designing the methodology based on stakeholder consultations. The framework and methodology derived combined at least five issue areas corresponding to the following disciplines1) public health 2) socio-economic 3) policy 4) veterinary and 5) community and environment. Methods used were questionnaires, observation, focus groups, and in-depth interviews. In addition, a microbiological risk assessment approach was employed to identify hazards and critical factors of slaughtering process affecting food safety and emerging food born pathogen risk. Combining this with stakeholder knowledge and attitudes provided the basis for identifying feasible and sustainable interventions. This study revealed that there were complex factors affecting to the hygienic management of the slaughterhouse. The study also demonstrated the potential of an integrative, participatory approach for addressing a critical problem at the interface of rural development and public health. It may serve as a useful model as basis for study and intervention for other similar transdisciplinary challenges.